2017
DOI: 10.1007/s00240-017-0973-2
|View full text |Cite
|
Sign up to set email alerts
|

Do renal stones that fail lithotripsy require treatment?

Abstract: The rates of extracorporeal shock wave lithotripsy (SWL) appear stable in the UK. However, there is little evidence on the natural history of these calculi if SWL fails. We set to look at the effectiveness of SWL in patients with a single, previously untreated renal stone and the natural history of those stones that failed treatment. We retrospectively reviewed all data from our prospectively collected database of patients undergoing a first treatment for a single renal stone between October 2010 and November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Risk of developing symptoms over at least 24 months of follow‐up in patients who were asymptomatic at baseline with stones or residual fragments of ≤10 mm was described by eight of the included studies [26,28–33,35]. Rates of symptoms were reported between 0% and 59.4% [30,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Risk of developing symptoms over at least 24 months of follow‐up in patients who were asymptomatic at baseline with stones or residual fragments of ≤10 mm was described by eight of the included studies [26,28–33,35]. Rates of symptoms were reported between 0% and 59.4% [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…[34] also failed to find a significant difference between rates of intervention according to stone size, with rates of 5%, 9.5% and 14.3% for stones of <5, 5–10 and >10 mm, respectively ( P = 0.477). One study suggested that intervention is frequently triggered by pain symptoms and reported this to be the case in 73% (27/51) of interventions in a total of 169 patients [35]. The Kang et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies of the natural history of CIRFs after SWL and RIRS have shown that that the majority of CIRFs (approx. 56-78%) do spontaneously pass or requires no further treatment [8,[26][27][28][29]. This still leaves a significant proportion (approx.…”
Section: Discussionmentioning
confidence: 99%